Design of New Openers of ATP-Sensitive Potassium Channels of the Cell Membranes - Strutynskyi, R.B.; Strutynska, N.A.; Maximyuk, O.P.; Platonov, M.O.; Boyko, O.M.; Vasylchenko, A.V.; Fedyanovich, I.N.; Dosenko, V.E.; Krishtal, O.A. (Science and Innovation, 2024)
Two innovative libraries (413 cyclosulfamides and 709 orthopyridine sulfamides) of potential new openers of ATPsensitive potassium channels of cell membranes have been created. It is shown experimentally that, at least, ten new original compounds have properties of pharmacological openers of the channels. Seven compounds (Z851154982, Z56762024, Z1269122570, Z31153162, Z45679561, Z756371174, and Z649723638) open channels of both the sarcoplasmic and the mitochondrial membranes. Z734043408 compound is a strong activator of aforementioned channels of the sarcolemmal membrane only. Z31197374 and Z666664306 compounds have showed the affinity only to the КATP channels of the mitochondrial type. The results of the research can be used by pharmaceutical companies and research institutes.